The effect of follicular and ampullary fluid extracellular vesicles on bovine oocyte competence and in vitro fertilization rates - Zohreh Pakniyat; Mehdi Azari; Mojtaba Kafi; Mehran Ghaemi; Seyed Mohammad Amin Hashemipour; Amin Safaie; Davoud Eshghi (PLoS ONE, 2025)
Follicular fluid from preovulatory follicles as well as ampullary fluid from slaughtered cows at the early metestrus were collected for isolation of EVs. Excellent and good quality bovine oocytes were selected and distributed into four groups: control group which did not receive EVs, the FFEV group which were exposed to 40 μg/ml of follicular fluid EVs for the first 18 hours of the culture, the FFAFEV group which received 40 μg/ml of follicular fluid EVs for the first 18 hours of the culture, followed by 3.4 μg/ml of ampullary fluid EVs for the remaining 4.5 hours, and the AFEV group which were exposed to 3.4 μg/ml of ampullary fluid EVs for the final 4.5 hours of the culture. After a total incubation period of 22.5 hours, the COCs were evaluated for nuclear maturation, expression of some relevant genes, and Raman spectra from different areas of the representative matured oocytes (Experiment 1). In addition, fertilization rate of the oocytes was assessed after addition of EVs to the maturation medium (Experiment 2). The maturation and fertilization rates, as well as the expression of TNFAIP6, HAS2, and GDF9 genes, were significantly higher in the EVs treatment groups compared to the control group (p ≤ 0.05). Furthermore, the Raman microspectroscopy revealed a higher number of mitochondria (1602 cm-1), increased levels of unsaturated lipids (1655 cm-1) and a favorable phenylalanine to carbohydrate ratio (1002/1037, serving as a marker for oocyte quality, in the FFAFEV group compared to the control group. Additionally, there was a lower concentration of saturated lipids (2883 cm-1) in the FFAFEV group than in the control group. In conclusion, our findings showed that supplementation of the oocyte maturation media with follicular and ampullary fluid EVs positively influenced oocyte quality and enhanced in vitro maturation, fertilization rates, and the relevant gene expression.